Neuroimaging of pain mechanisms. - Tracey, I (2007)
PURPOSE OF REVIEW: Functional neuroimaging has made a huge impact scientifically, not least within the field of pain research. The noninvasive identification of pain mechanisms that underpin chronicity, such as central sensitization and other amplification processes related to the cognitive or emotional state of the patient, is of considerable interest to the clinical pain community and pharmaceutical industry. Relating data to a person's specific pain report or measure of pain relief provide a clearer understanding of the mechanisms driving and maintaining this complex experience. It is timely, therefore, to review the advances in neuroimaging applications to pain. RECENT FINDINGS: New data have emerged to further support the descending modulatory system's critical role in chronic pain. The neural correlates that underpin tonic, ongoing and spontaneous pain in patients are being identified. Additionally, the prefrontal cortex is emerging as a critical brain region for pain processing, especially in patients. Finally, data from structural and molecular imaging studies are highlighting the extent of damage the brain sustains when patients live with their chronicity unrelieved. SUMMARY: Neuroimaging tools have advanced our understanding of central pain mechanisms in normals and patients, forcing us to reconsider issues related to diagnosis and provision of treatment.